Third intracellular loop of HCMV US28 is necessary for signaling and viral reactivation - Medica, Samuel; Denton, Michael; Diggins, Nicole L.; Kramer-Hansen, Olivia; Crawford, Lindsey B.; Mayo, Adam T.; Perez, Wilma D.; Daily, Michael A.; Parkins, Christopher J.; Slind, Luke E.; Pung, Lydia J.; Weber, Whitney C.; et al. (Journal of virology, 2025)
Human cytomegalovirus (HCMV) is a β-herpesvirus that infects between 44% and 100% of the world population. Primary infection is typically asymptomatic and results in the establishment of latent infection within CD34 + hematopoietic progenitor cells (HPCs). However, reactivation from latent infection remains a significant cause of morbidity and mortality in immunocompromised individuals. The viral chemokine receptor US28 influences various cellular processes crucial for viral latency and reactivation, yet the precise mechanism by which US28 functions remains unclear. Through mutational analysis, we identified key residues within the third intracellular loop (ICL3) of US28 that govern G-protein coupling, downstream signaling, and viral reactivation in vitro and in vivo . These findings offer novel insights into how US28 manipulates host signaling networks to regulate HCMV latency and reactivation and expand our understanding of HCMV pathogenesis.